Sezonowe zmiany stanu biomasy w runie lasu grądowego Stellario holosteae-Carpinetum betuli - Rawlik, Mateusz; Jagodziński, Andrzej; Janyszek, Sławomir (Leśne Prace Badawcze, 2012)
We studied seasonal changes in the understorey biomass of an oak-hornbeam forest association Stellario holosteae-Carpinetum betuli . Samples were collected weekly during the most active period of growth of the herbaceous layer (April-May 2010), and every two weeks for the remainder of the growing season (June-October). Quadrates of 0.36 m 2 were sampled from 7-9 randomly selected locations within the plant community. The plants harvested were separated by species, then oven-dried and weighed. We found statistically significant differences in aboveground understorey biomass over the periods of biomass harvesting. For example, the average plant biomass (produced in 2010 and previous years) was smallest on March 20 th (40.6 kg/ha), whereas the biomass was greatest on May 15 th (393.8 kg/ha). The mean biomass of the understorey vegetation during spring was 324.1 kg/ha, while the mean biomass for summer and early autumn was 108 kg/ha. The smallest plant biomass (produced during 2010) was on March 20th (18.3 kg/ha) and the largest on May 15 th (378.4 kg/ha). Only a few herbaceous species dominated the total community biomass production. For example, from March 20 th to May 29 th the biomass of Anemone nemorosa was the highest at ca. 74% of total understorey herbaceous plant biomass, while Ficaria verna was second with 8%. During the next harvesting period (June-October) Galeobdolon luteum and Galium odoratum comprised 53.2% of total plant biomass harvested. It is evident that the highest biomass production is during the spring when the geophytes develop.